IMPLEMENTATION OF THE PRINCIPLES OF SUB-DISTRICT LEADERSHIP IN ORDER TO SUPPORT THE REALIZATION OF GOOD GOVERNANCE - USMAN, ANDRIE (Sam Ratulangi University, 2014)
Sub-District head is the supreme leader of government in the district. And to be a good leader, then certainly in performing their duties a sub-district head should understand his duty as a leader and also should have the principles of good leadership which is capable of Implementation. Similarly, the head of sub-district authorities, in carrying out the task of leadership as head of the district, there are certain principles that must be applied in their work environment. The principles of Â good governance is something that should be a reference and things that should be implemented, in leadership of district arbitrary. Seeing the apparatus performance in this case the staffs and districts leadership, the application of the principles of leadership is indispensable in order to create a good governance and appropriate to advance the image as a responsible government and that can be expected, although such things about that leadership principles not necessarily be fully done very well without blamed and deficiencies in running it, see the performance, duties and functions of the sub-district leaders in this case the sub-district head.